Incremental healthcare resource utilization and costs for patients with cervical, vaginal, vulvar, anal, and oropharyngeal cancer in the United States. (2nd September 2021) - Prabhu, Vimalanand; Kathe, Niranjan; Saxena, Kunal; Walia, Anuj; Markan, Riddhi; Myers, Evan; Einstein, Mark
Abstract: Introduction: Human papillomavirus (HPV) cause cancers in a variety of anatomic sites presenting at various stages of disease. Current economic assessments rely on HPV-related cancer cost estimates from data prior to the launch of the nonavalent HPV vaccine (2014). The goal of the present study was to assess and describe the current direct medical care burden of HPV-related cancers in the US. Methods: Using Clinformatics Data Mart, patients in the US who were newly diagnosed with cervical, vulvar, vaginal, anal, and oropharyngeal cancers between 2012 and 2015 were compared to non-cancer matched (propensity score) controls. Health care resource utilization and direct medical cost (2020 USD) were assessed over a 2-year follow-up period following index diagnosis from a payer perspective. The cost for censored time was estimated using generalized linear model while adjusting for survival probability using cox-proportional hazard model. Confidence intervals were calculated with bootstrapping technique. Results: The analyses included 4128 cervical, 1580 vulvar, 538 vaginal, 1827 anal, and 6106 oropharyngeal cancers and matched controls. Cases and controls had similar baseline clinical characteristics and length of follow-up. The 2-year incremental direct medical costs were 93, 272, 81, 676, 141, 096, 129, 366, and 134, 045 for cervical, vulvar, vaginal, anal, and oropharyngeal cancers respectively. Outpatient care costs was the biggest driver of the total incremental medical costs. Most cancer costs were incurred during the first 6 months of follow-up and then stabilized during follow-up. Conclusion: HPV-related cancers are responsible for substantial health care expenditure each year.